Women Identity on FacebookProfiles. A sociolinguistic perspective: College of Basic Education. - Naji Kamil, . Mokhalad (Journal of College of Education, 2017)
The current study attempts to investigate the construction of women identity on social network, namely Facebook Profiles. Generally speaking, it is recognized that women are more self-conscious than men in expressing their character. As its problem, this study investigates the linguistic characteristics of women's language on Facebook profiles. Thus, the current study aims at finding out the main characteristics of women identity online communication. The study hypothesizes that women have recognizable linguistic characteristics that reflect their character online communication. The questionnaire represents the main tool of collecting data. The study has reached a number of conclusions that validate the hypothesis of the study.